Characterization and management of ganoderma lucidum inciting basal stem rot of coconut - Yunus C (Department of Plant Pathology, College of Horticulture, 2012)
The present study on “ Characterization and management of Ganoderma lucidum inciting basal stem rot of coconut ” was undertaken in the Department of Plant Pathology, College of Horticulture, Vellanikkara during 2010-2012 with an aim to isolate the pathogen associated with the disease and to study the cultural, morphological and pathogenic characters of different isolates of the pathogen, symptomatology of the disease, host range and effective management of the pathogen using bio-control agents, phytoextracts and selected fungicides. Purposive sampling surveys were conducted and the occurrence of basal stem rot disease of coconut was observed through out Kerala. The isolation of pathogen from basidiocarps yielded eight isolates of Ganoderma sp. which produced fruiting body in saw dust- rice bran substrate. The pathogenicity of these isolates was tested and observed yellowing, drying and drooping of leaves of coconut seedlings inoculated with all isolates except the isolate GT- from Trivandrum. Basidiocarp formation was noticed only in one seedling inoculated with the isolate GV from Vellayani and reisolation of pathogen was done from this basidiocarp. Symptomatology of the disease under natural and artificial conditions was studied. Under field condition the typical symptom of BSR disease viz., yellowing and drooping of leaves, stem bleeding and basidiocarp formaton were observed in all surveyed areas but all the typical symptoms of disease were not observed under artificial condition. The cultural characters of all the isolates of pathogen were studied on four media viz., Potato dextrose agar, Czapek’s (DOX) agar, Richard’s agar and Soil extract agar media. All isolates produced white mycelial growth on all media but variations in texture, mycelial type, and colour change of mycelium, exudates production and formation of aberrant fruiting body were observed. PDA was found to be the best medium for the growth of pathogen in which all isolates recorded highest growth rate. The pathogen preferred a temperature range of 30-350C and neutral to acid pH of 5-7 for the growth. Slight variation in growth rate was observed under light and darkness. Basidiocarps showed variations in the morphological characters and were stipitate in all isolates except GC from Chirakkacode and GVe from Vettikkal, semicircular to conical shaped, yellowish red to reddish brown with smooth to waved margin, creamy white to brown pore surface, 4.4 – 12.0 x 2.6- 17.0 cm size, 1-10 mm pore length, 139- 254 x 122 – 190 μm pore diameter and 2-10 mm flesh thickness. Basidiospores were brown, ovate to ellipsoidal, truncated apex, double walled with inter wall pillars separating two walls. The size of these basidiospores showed variation in the range of 4.8-13 x 4.5-7.0μm with a spore index of 1.15-1.7. It was trimitic, with generative hyphae hyaline, thin walled, branched, septate and clamped. Reddish brown pigmented skeletal hyphae and colourless binding hyphae were noticed. Based on these observations the eight isolates of the pathogen were identified as Ganoderma lucidum (Leys) Karst. Regarding the in vitro management of the pathogen, two isolates of T. virens and one isolate of T. viride were isolated from rhizophere soil and were proved equally effective with the reference culture, T. viride and T. harzianum in inhibiting the growth of pathogen. Mycoparasitism and production of non volatile metabolites were found to be the mechanisms exhibited by the selected Trichoderma spp. The bacterial antagonists obtained from rhizosphere soil and the reference culture P. fluorescens recorded less than 50 percent inhibition on the growth except in cases of few isolates of the pathogen. It was observed that the selected bacterial antagonists were not much effective in inhibiting the pathogen compared to fungal antagonists. Among the phytoextracts, Azadirachta indica at 20 per cent concentration was found the most effective and recorded more than 50 percent inhibition on the growth of pathogen over control. It was followed by Musa sp. at 10 per cent concentration. The in vitro evaluation of fungicides showed that flusilazole, hexaconazole and iprobenphos at 0.2 per cent concentration were the most effective and recorded cent per cent inhibition on the growth of all isolates of pathogen. The study on the host range of G. lucidium revealed that the seedlings of arecanut, breadfruit, acacia and jack fruit showed yellowing and drooping of leaves and finally wilting of all the seedlings were observed